Media Coverage of Conflicts in Nigeria: Comparative Analysis of Two Nigerian Newspaper - Opeyemi, Ataiyero Adedoyin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The mass media serve as important players in peace building during conflicts. With their ability to pervade spaces and direct people’s attention on important issues, they can either play a key role in escalating or de-escalating conflicts. This research is conducted to compare the coverage of conflict between two national dailies in Nigeria within a 12 months period in 2018. The issue of conflict is an important one in Nigeria. Being a large country with two main religions and multiple ethnic groups, Nigeria has experienced different forms of conflict since the 1960s. These conflicts have caused a breakdown in society, loss of lives and property and have heavily affected how the various tribes and ethnic groups in Nigeria relate with each other. A sample of 46 newspaper edition was systematically selected for both newspapers (n = 92). Three questions guided this research; what themes are dominant in the coverage of conflicts in the Punch and Thisday newspapers between January and December 2018? Do the Nigerian press aggravate conflict by reporting winners and losers in a conflict? Do the Nigerian media assign blames in their coverage of conflict in Nigeria? The study is theoretically situated within agenda setting theory and peace journalism. The findings of the research determined that the Nigerian media exercised restraint in their coverage of conflict in the period of research. It was not clear if the observed restraint was a deliberate attempt at practicing peace journalism. In the future, research should be conducted to determine the perception of journalists on peace journalism in Nigeria. Keywords: Mass media, Conflict, Peace Journalism, Peace Building, Nigeria

ÖZ: Kitle iletişim araçları çatışmalar sırasında barış inşasında önemli oyuncular olarak hizmet ederler. Mekanları kullanma ve insanların dikkatini önemli konulara yönlendirme yetenekleri ile, çatışmaları tırmanmada veya tırmandırmada kilit rol oynayabilirler. Bu araştırma, 2018'de 12 aylık bir süre içinde Nijerya'daki iki ulusal günlük gazete arasındaki çatışmanın kapsamını karşılaştırmak için yapılmıştır. Çatışma konusu Nijerya'da önemli bir konudur. İki ana dine ve çok sayıda etnik gruba sahip büyük bir ülke olan Nijerya, 1960'lardan beri farklı çatışma biçimleri yaşamıştır. Bu çatışmalar toplumda bir bozulmaya, can ve mal kaybına neden oldu ve Nijerya'daki çeşitli kabilelerin ve etnik grupların birbirleriyle ilişkilerini büyük ölçüde etkiledi. Her iki gazete için sistematik olarak 46 günlük Orrehlem olarak gazete seçildi (n = 92). Bu araştırmaya üç soru yön verdi; Ocak ve Aralık 2018 tarihleri arasında Punch ve Thisday gazetelerinde yaşanan çatışmaların kapsamına giren konular nelerdir? Nijerya basını, bir çatışmada kazananları ve kaybedenleri bildirerek çatışmayı ağırlaştırıyor mu? Nijerya medyası Nijerya'daki çatışmaları kapsamakla suçluyor mu? Çalışma teorik olarak gündem belirleme teorisi ve barış gazeteciliği içinde yer almaktadır. Araştırmanın bulguları, Nijerya medyasının araştırma döneminde çatışmaları kapsama konusunda kısıtlama kullandığını tespit etti. Gözlemlenen kısıtlamanın barış gazeteciliğini uygulamak için kasıtlı bir girişim olup olmadığı belli değildi. Gelecekte, gazetecilerin Nijerya'da barış gazeteciliği hakkındaki algılarını belirlemek için araştırmalar yapılmalıdır. Anahtar Kelimeler: Kitle iletişim araçları, Çatışma, Barış Gazeteciliği, Barış İnşası, Nijerya.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Communication and Media Studies, 2020. Supervisor: Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; Journalists--Newspapers--Media Coverage--Conflicts--Nigeria; Journalists--Press coverage--Mass Media--Peace Journalism; Mass media; Conflict; Peace Journalism; Peace Building; Nigeria